Examining Adolescents’ Technology Addiction Levels Before and After COVID-19 Pandemic - Renan Seker; Tezcan Kartal; Adem Tasdemir; Ibrahim Serdar Kiziltepe (Journal of Education in Science, Environment and Health)
Technology may lead to many new problems, especially for students at high school level. The ease of using and accessing technology increases the risk of the younger pupils’ addiction to technology. Problematic uses of technology, especially among high school students, include internet use, instant messaging, online gaming, social networking and computer use. Given the large young population in Turkey, it is important to evaluate the internet-based technologies’ potentially positive effects as well as their undesirable effects. For this reason, the technology addiction levels of high school students before and after the pandemic and the change in technology addiction based on demographic characteristics (owning a computer, socio-economic level, time spent on social networks, grade level) were investigated. The cross-sectional survey method, one of the descriptive research designs, was used in the research. Participants consisted of 304 high school students selected via random sampling method. “Technology Addiction Scale” was used in the research. The data of the study was compared with the data of another study conducted with the same measurement tool and a similar sample before the pandemic. As a result of the research, when the addiction levels of adolescents before and after the pandemic are compared, it is seen that the students in the low-risk group move towards the risky and the addicted groups. In addition, it was determined that the percentage of highly-addicted students increased. It was observed that the students' highest addiction levels were in instant messaging, website use, social network use and online gaming, respectively. While the addiction levels of the participants varied based on the time spent on social networks and online gaming, the interaction effect between owning a computer and the family socioeconomic level also caused significant differences.